Impact of cavotricuspid isthmus ablation for typical atrial flutter and heart failure in the elderly—results of a retrospective multi-center study - Boxhammer, Elke; Bellamine, Meriem; Szendey, Istvan; Foresti, Mike; Bonsels, Marc; Kletzer, Joseph; Jirak, Peter; Topf, Albert; Kraus, Johannes; Fiedler, Lukas; Dieplinger, Anna-Maria; Hoppe, Uta C.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction While in the CASTLE-AF trial, in patients with atrial fibrillation and heart failure with reduced ejection fraction, interventional therapy using pulmonary vein isolation was associated with outcome improvement, data on cavotricuspid isthmus ablation (CTIA) in atrial flutter (AFL) in the elderly is rare. Methods We included 96 patients between 60–85 years with typical AFL and heart failure with reduced or mildly reduced ejection fraction (HFrEF/HFmrEF) treated in two medical centers. 48 patients underwent an electrophysiological study with CTIA, whereas 48 patients received rate or rhythm control and guideline-compliant heart failure therapy. Patients were followed up for 2 years, with emphasis on left ventricular ejection fraction (LVEF) over time. Primary endpoints were cardiovascular mortality and hospitalization for cardiac causes. Results Patients with CTIA showed a significant increase in LVEF after 1 (p<0.001) and 2 years (p<0.001) in contrast to baseline LVEF. Improvement of LVEF in the CTIA group was associated with significantly lower 2-year mortality (p=0.003). In the multivariate regression analysis, CTIA remained the relevant factor associated with LVEF improvement (HR: 2.845 CI:95% 1.044-7.755; p=0.041). Elderly patients (≥ 70 years) further benefited from CTIA, since they showed a significantly reduced rehospitalization (p=0.042) and mortality rate after 2 years (p=0.013). Conclusions CTIA in patients with typical AFL and HFrEF/HFmrEF was associated with significant improvement of LVEF and reduced mortality rates after 2 years. Patient age should not be a primary exclusion criterion for CTIA, since patients ≥70 years also seem to benefit from intervention in terms of mortality and hospitalization.